2018
DOI: 10.1016/j.apacoust.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Review of active noise control techniques with emphasis on sound quality enhancement

Abstract: The traditional active noise control design aims to attenuate the energy of residual noise, which is indiscriminative in the frequency domain. However, it is necessary to retain residual noise with a specified spectrum to satisfy the requirements of human perception in some applications. In this paper, the evolution of active noise control and sound quality are briefly discussed. This paper emphasizes on the advancement of active noise control method in the past decades in terms of enhancing the sound quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…Secondly, the distance ratio is important. As can be seen from equation (6), any change in the location of the detector or the observer with respect to the noise sources will be reflected in the transfer function for the controller. The critical geometrical condition for optimal cancellation performance can be expressed as…”
Section: System Description With Geometry-related Considerationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Secondly, the distance ratio is important. As can be seen from equation (6), any change in the location of the detector or the observer with respect to the noise sources will be reflected in the transfer function for the controller. The critical geometrical condition for optimal cancellation performance can be expressed as…”
Section: System Description With Geometry-related Considerationsmentioning
confidence: 99%
“…Using equations (6) and (8), it can be shown that that the controller will have an infinite gain, under the condition in equation (8), for the noise level at the observer point to be reduced to zero. However, this cannot be realised in real life or in the simulation experiments.…”
Section: System Description With Geometry-related Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The passive control approach uses absorbers or barriers to attenuate the noise level, which transforms the acoustic energy to heat energy, and it has already demonstrated superior performance in high-frequency noise reduction. [4][5][6] However, for low-frequency noise, the passive approach is expensive and inconvenient, as increasing acoustic noise wavelength requires a larger size absorbing or damping material. To attenuate low-frequency noise, the active noise control (ANC) method, which is essentially based on the principle of superposition, is proposed.…”
Section: Background and Literature Reviewmentioning
confidence: 99%